Drug-induced QT interval prolongation and major adverse cardiac events: Meta-analysis of randomized controlled trials - Garcia, M; Tsang, J; Lohit, S; Deng, F; Chang, O; Cairns, K; Rehman, N; Hijazi, W; Mbuagbaw, L; Holbrook, AM (My University, 2023)
Background: QT-prolonging medications (QTPMeds) have become a major source of clinical concern regarding medication-related major adverse cardiac events (MACE); MACE events are rare and it is not clear if all QTPMeds create harm, or in which circumstances. Objectives: Systematically review the study data on the association between QTPMedsand MACE; here we report on a subset of randomized trials. Discussion: Most trials are not statistically powered to detect MACE
Keywords: QT-prolonging medications; medication-related major adverse cardiac events; systematic review